Screening mechanisms and student responses in the college market. (February 2015) - Smith, Jonathan; Hurwitz, Michael; Howell, Jessica
Abstract: In light of the sizeable financial and time investments associated with obtaining a postsecondary degree, the choice of where to apply and enroll should be a deliberate and thoughtful process. In this paper we exploit changes in application fees and admissions essay requirements, to demonstrate that students strongly respond to small costs in the college application process. Using a new method to identify major competitors of each college, we find that these small screening mechanisms negatively impact application volume and divert student applications to colleges to which they otherwise would not have applied. There is limited evidence that measures of enrollment and retention are affected. Highlights: Colleges frequently change the way they screen potential applicants. Increasing application fees by as little as $10 decreases applications. Requiring an application essay decreases applications by 6.5%. Applications typically shift to major competitors. There are few measurable effects on the composition of matriculants or match.